Biscogniauxia nummularia infecting beech (Fagus sylvatica) trees and sympatric plants of the sedge Carex brevicollis. Issue 4 (28th May 2015) - Zabalgogeazcoa, I.; Pedro, J.; Canals, R. M.; Sieber, T.
Summary Biscogniauxia nummularia is known for its association with beech (Fagus sylvatica), on which it occurs as a saprotroph and a pathogen causing strip cankers following water stress. This fungus has also been reported as a dominant endophytic species in plants of the sedge Carex brevicollis growing in the understory of beech forests and adjacent grasslands in Sierra de Urbasa (Navarre, Spain). In this area, stromata of B. nummularia were observed in dead and living wood of beech trees at several locations where plants of C. brevicollis also contained the fungus as an endophyte. Pure cultures obtained from stromata of B. nummularia on F. sylvatica trees were compared to endophytic isolates from symptomless C. brevicollis. Culture morphology and micromorphology as well as rDNA sequences of the internal transcribed spacer (ITS) regions were identical, suggesting that B. nummularia from beech can also live endophytically in C. brevicollis. It is unknown whether the endophytic strains of Carex might have a role as an inoculum source for the infection of beech trees, or whether they represent a dead end in the life cycle of the fungus.